Impact of the teacher education curriculum on the development of 21st-Century skills: Pre-service teachers’ perceptions - Mensah Prince Osiesi; Sylvan Blignaut (Social Sciences and Humanities Open)
This study examined the perceptions of pre-service teachers (PTs) at Nelson Mandela University in South Africa on the role of the Teacher Education Curriculum (TEC) in the Development of 21st-Century Skills (21CS) among PTs. Underpinned by the theories of self-regulated learning, Technological Pedagogical Content Knowledge, and Planned Behaviour, the study adopted the descriptive survey research type of the non-experimental design. The study population comprised all PTs in the education faculty. 411 PTs were selected via purposive and simple random sampling techniques. PTs' Perceived 21CS Development Questionnaire (r = 0.97) was used in collecting the study’s data, which were analysed using Hayes macro process in SPSS version 26.0. Findings indicate that the South African TEC largely inculcates 21CS in PTs, the prevalent 21CS among PTs are collaborative, communication, critical thinking, and creativity skills (in that order), and PTs’ excess academic workloads, lack of digital competencies and literacy, and inadequate assessment of ICT-related skills are the main challenges militating against their development of 21CS. The study concludes that PTs positively perceive the TEC's potency in developing their 21CS for future teaching competencies and efficiencies. Recommendations are made.